Preferensi Konsumen Gen Z terhadap Tren Customization dalam Produk Pakaian untuk Pengembangan Strategi Pemasaran - Anjangsari Khaida Asaro (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
The global fashion industry continues to experience rapid growth, driven by changes in consumer preferences that increasingly emphasize personalization in clothing products. This study aims to analyze Generation Z's preferences for customization trends in fashion products and identify their impact on marketing strategies in the fashion industry. A qualitative approach with a descriptive method was used to understand the factors influencing Gen Z's preferences when selecting customizable fashion products. Primary data was collected through interviews with Gen Z consumers who are active shoppers on e-commerce platforms. The results show that 60% of Gen Z consumers are interested in customizable fashion products, with the main reasons being to express individuality and enhance emotional attachment to the brand. Social media, especially Instagram and TikTok, plays a significant role in shaping consumer preferences, as more than 70% of informants acknowledge that influencer recommendations influence their decision to purchase customized products. Based on these findings, it can be concluded that customization is not just an additional feature but a marketing strategy that can enhance consumer loyalty. Recommendations from this study include implementing personalized marketing strategies, improving customization features on e-commerce platforms, and collaborating with influencers to expand market reach.